Socioeconomic factors affecting exclusive breastfeeding in the first 6 months of life - Javad Nazari; Abbas Esmaili; Eshrat-Sadat Mousavi; Pari Mirshafiei; Saeed Amini (Hygeia Press di Corridori Marinella, 2021)
Introduction: Despite the well-known positive effects of exclusive breastfeeding (EBF) in the first 6 months of life, several studies have indicated its inadequacy in Iran. This study has investigated the socioeconomic factors affecting EBF in the first 6 months of life. Methods: The study population included 6- to 12-month-old children referred to Arak healthcare centers with their mothers for vaccination and healthcare in 2019. Sampling was performed according to Cochran formula. The questionnaires were completed by asking mothers and also reference to the family documents. The relationship between EBF and household socioeconomic variables was examined using Kaplan-Meier survival analysis. The multivariate logistic regression was used to assess adjusted and unadjusted odds ratios for factors affecting EBF and the relationship between household variables and breastfeeding. Results: Mothers completed a total number of 517 questionnaires (97%). Working mothers (OR = 2.3 [1.77, 2.91]), mothers with higher education (OR = 1.02 [0.68, 1.35]) and higher physical activity (OR = 1) breastfed their infants more than others up to 6 months (p < 0.05). There was no significant relationship between sex of the child, household income, maternal BMI, pregnancy complications, previous abortion, and type of delivery with EBF (p > 0.05). Conclusion: The results indicated that mothers who belonged to low socioeconomic groups breastfed their infants less than other groups. This necessitates planning and taking interventional healthcare, educational, and financial support measures in this group.